2017
DOI: 10.1002/ejoc.201700321
|View full text |Cite
|
Sign up to set email alerts
|

First Asymmetric Total Synthesis and Insight into the Structure of Laurenidificin

Abstract: (+)‐Laurenidificin has a fused bis‐THF skeleton and an enyne structure in its side chain. It is known that the bis‐THF skeleton is cis,cis fused, and the absolute configuration at the C6 position is R, but the whole structure has not been determined. We synthesized one possible isomer of (+)‐laurenidificin by using intramolecular double bromoetherification as a key step. Treatment of a protected (E,E)‐diene diol with 2,4,4,6‐tetrabromo‐2,5‐cyclohexadienone as the halogenating agent afforded a cis,cis‐fused bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The rst asymmetric total synthesis of lau-renidicin has deduced that it possesses 6R,7R,9R,10R,12R,13S conguration. 397 An asymmetric total synthesis of isodehydrothyrsiferol has revealed that the majority of its chiral centres are enantiomeric with those of other squalene-derived thyrsiferol triterpenoids. 398 Y-Maze experiments have demonstrated that (+)-elatol isolated from Laurencia dendroidea is an attractant for the sea hare Aplysia brasiliana.…”
Section: Red Algaementioning
confidence: 99%
“…The rst asymmetric total synthesis of lau-renidicin has deduced that it possesses 6R,7R,9R,10R,12R,13S conguration. 397 An asymmetric total synthesis of isodehydrothyrsiferol has revealed that the majority of its chiral centres are enantiomeric with those of other squalene-derived thyrsiferol triterpenoids. 398 Y-Maze experiments have demonstrated that (+)-elatol isolated from Laurencia dendroidea is an attractant for the sea hare Aplysia brasiliana.…”
Section: Red Algaementioning
confidence: 99%
“…4 The validity of our proposal was soon confirmed by the total synthesis of 3 by Fujioka et al 5 Our strategy to construct central bis-tetrahydrofuran (bis-THF) ether relied on the stereospecific ring contraction of the sterically congested bromolactone (12S)-7 that was prepared by halolactonization, reduction, and α-bromination from the monocyclic carboxylic acid 6 4 (Scheme 1). This strategy was proved to be valuable for the synthesis of other natural bicyclic ethers such as (−)-aplysiallene (5) and communiol E, where the hydrogens at C2 (=C12−H) and C4 (=C10−H) of the THF ring are in a trans relationship (Figure 1). 4,6 The predominant trans selectivity during ring contraction is ascribed to the backside attack of alkoxide A to bromine-bound carbon through an intramolecular nucleophilic substitution process.…”
Section: ■ Introductionmentioning
confidence: 70%
“…In 2016, we achieved the synthesis of a stereoisomer of (+)-laurenidificin ( 4 ), which led to a proposal of the absolute configuration of the natural product as structure 3 . The validity of our proposal was soon confirmed by the total synthesis of 3 by Fujioka et al Our strategy to construct central bis-tetrahydrofuran (bis-THF) ether relied on the stereospecific ring contraction of the sterically congested bromolactone (12 S )- 7 that was prepared by halolactonization, reduction, and α-bromination from the monocyclic carboxylic acid 6 (Scheme ). This strategy was proved to be valuable for the synthesis of other natural bicyclic ethers such as (−)-aplysiallene ( 5 ) and communiol E, where the hydrogens at C2 (=C12–H) and C4 (=C10–H) of the THF ring are in a trans relationship (Figure ).…”
Section: Introductionmentioning
confidence: 97%